KUALIFIKASI STANDARISASI DAN LISENSI ADVOKAT ASING DALAM RANGKA IMPLEMENTASI GATS (GENERAL AGREEMENT ON TRADE IN SERVICES) - FX Joko Priyono (Faculty of Law, Universitas Diponegoro, 2010)
Profeesional service including legal service is apart of service covered by GATS (General Agreement on Trade in Services). Indonesia as contracting party has obligation to adjust some rules regarding market access to foreign law firm and lawyer. At the moment Law Number 18 of 2003 on Advocate has restricted them to practice in Indonesia and only as an employee of the law firm. It can't be ignored while globalization of legal service has been happening due to business activities of transnational corporation. Qualification, standarizationand licence of foreign lawyer is very significant in order to do interact between domestic and foreign lawyer. Closing the market access will make no progress of domestic lawyer. Experience, legal education, test of advocate organization, ability of speaking Indonesia language, training, honest and good reputation. License is promoted by limited approach that admitting foreign lawyer to practice home country law, international law and third country law. Representation before the court and rendering legal advice are prohibited at all.Kata Kunci : GATS, globalization of legal service, and qualification, standarization and licence of foreign lawyer